Urban hunters : dealing and dreaming in times of transition - Højer, Lars; Pedersen, Morten Axel, 1969- (Eurasia past and present., 2019)
An ethnography of the Mongolian capital city of Ulaanbaatar during the nation's transition from socialism to a market-based economic system. Urban Hunters is an ethnography of the Mongolian capital city, Ulaanbaatar, during the nation's transition from socialism to a market-based economic system. Following the Soviet Union's collapse in 1991, Mongolia entered a period of economic chaos characterized by wild inflation, disappearing banks, and closing farms, factories, and schools. During this time of widespread poverty, a generation of young adults came of age. In exploring the social, cultural, and existential ramifications of a transition that has become permanent and acquired a logic of its own, Lars Hojer and Morten Axel Pedersen present a new theorization of social agency in postsocialist as well as postcolonial contexts.